132k views
7 votes
What expression is equivalent to 5(1/3x+7)-3(1/2x-4)

User MrDuk
by
4.8k points

2 Answers

5 votes
5 (1/3x + 7) - 3 (1/2x - 4)

1/3x = x/3

1/2x = x/2

5 (x/3 + 7) - 3 (x/2 - 4)

Expand with the multiplier 5

= 5x/3 + 35 - 3 (x/2 - 4)

Expand with the multiplier -3

= 5x/3 + 35 - 3x/2 + 12

Simplify the problem

= x/6 + 47

Therefore 5 (1/3x + 7) - 3 (1/2x - 4) is equivalent to x/6 + 47
User Nick Jonas
by
5.2k points
11 votes

Explanation:

5/3x +35-3/2x+12=0

5/3x -3/2x+35+12=0

1/6x+47=0

1/6x=-47

divide through by 6x

×=1/282

User Fisseha Berhane
by
4.9k points